An Experimental Ethics Approach to Robot Ethics Education - Williams, Tom; Zhu, Qin; Grollman, Daniel (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
We propose an experimental ethics-based curricular module for an undergraduate course on Robot Ethics. The proposed module aims to teach students how human subjects research methods can be used to investigate potential ethical concerns arising in human-robot interaction, by engaging those students in real experimental ethics research. In this paper we describe the proposed curricular module, describe our implementation of that module within a Robot Ethics course offered at a medium-sized engineering university, and statistically evaluate the effectiveness of the proposed curricular module in achieving desired learning objectives. While our results do not provide clear evidence of a quantifiable benefit to undergraduate achievement of the described learning objectives, we note that the module did provide additional learning opportunities for graduate students in the course, as they helped to supervise, analyze, and write up the results of this undergraduate-performed research experiment.